Corporate social capital disclosure in integrated reports: a structural topic modelling approach - Arun Podayan; B Charumathi (Future Business Journal)
Abstract Corporate social capital disclosure is essential for communicating a company’s societal contributions to various stakeholders. Adopting integrated reporting has enhanced non-financial reporting practices, improving the transparency and quality of sustainability-related information for investors. This study investigates patterns of social capital disclosure in the integrated reports of Indian firms by applying Structural Topic Modelling (STM) to uncover latent themes. Using data from Nifty 100 companies between 2018 and 2022, nine key disclosure topics were identified. Among these, crisis management, women’s leadership, human rights, supplier relationships, and community engagement were most prominent, while educational programs and digital inclusion were significantly underreported. Topic correlations revealed that educational and digital initiatives are linked with community support and crisis management, whereas women’s leadership and human rights align with skill development and safety. These findings suggest that firms prioritise community-oriented themes to enhance social legitimacy and stakeholder trust, aligning with legitimacy and stakeholder theories. The underrepresentation of certain themes highlights areas for strengthening corporate social responsibility practices. This study offers a novel framework for analysing corporate disclosures using advanced machine learning techniques, with implications for promoting transparency, accountability, and future ESG research.